1998
DOI: 10.1577/1548-8675(1998)018<0537:rofsag>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Fish Size and Growth Rate to Migration of Spring Chinook Salmon Smolts

Abstract: We examined the relation of size and growth rate to downstream migration in yearling spring chinook salmon Oncorhynchus tshawytscha. A group of juvenile chinook salmon was graded by size into small and large categories; half the fish in each category were reared at an elevated temperature beginning in mid‐February, resulting in four distinct treatment groups: large–warm, large–cool, small–warm, and small–cool. Fish from warmwater treatment groups displayed significantly higher growth rates through the spring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 25 publications
6
55
0
Order By: Relevance
“…Size at release may also affect migration behavior, as larger smolts tend to migrate earlier or faster than smaller ones in freshwater systems (Ewing et al 1984;Giorgi et al 1997;Beckman et al 1998 smolt size on early marine migration patterns. In the Baltic Sea, larger Atlantic salmon smolts migrated shorter distances than smaller smolts (Kallio-Nyberg et al 1999;Jutila et al 2003;Saloniemi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Size at release may also affect migration behavior, as larger smolts tend to migrate earlier or faster than smaller ones in freshwater systems (Ewing et al 1984;Giorgi et al 1997;Beckman et al 1998 smolt size on early marine migration patterns. In the Baltic Sea, larger Atlantic salmon smolts migrated shorter distances than smaller smolts (Kallio-Nyberg et al 1999;Jutila et al 2003;Saloniemi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (Bilton et al 1982;Bilton 1984;Ward and Slaney 1988;Martin and Wertheimer 1989;Ward et al 1989;Henderson and Cass 1991;Beckman et al 1998;Friedland et al 2009) have shown that larger juvenile Pacific salmon survive better in the early marine environment than smaller individuals. Throughout our study, hatchery fish were consistently larger than the better surviving wild chinook salmon.…”
Section: Discussionmentioning
confidence: 99%
“…However, when predation is density dependent, early development and corresponding high growth rates as fry may increase an individual's exposure to predation risk and result in lower fitness (Sundstrom et al, 2005). In chinook salmon, juvenile growth rates are also positively correlated with the age and timing of smoltification, the physiological process of adapting to salt water (Beckman and Larsen, 1998), and with increased marine survival during the first winter at sea in coho salmon (Beamish et al, 2004). In contrast to these findings, a study in Atlantic salmon showed a negative correlation between pre-smolt size and post-smolt size, suggesting that the adaptive benefit of size varies across ages and species (Einum et al, 2002).…”
Section: Introductionmentioning
confidence: 86%